I think you guys will know that (-1)(-1)=1 as me too, however a lot of students still being confused of this! Therefore, I want someone to explain this simple thing with different ways that the students will know instantly.
Example
(-1)(-1)
=(-1)(-1)-1+1
=(-1)(-1+1)+1
=0+1
=1
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
The proof I have isn’t very simple, but it shows that (−a)⋅(−b)=ab is a direct consequence of the properties of numbers (or what we defined them to be). These properties are, of course, the following:
Associative law - addition
a+(b+c)=(a+b)+c
Additive identity
a+0=0+a=a
Additive inverse
a+(−a)=(−a)+a=0
Communtative law - addition
a+b=b+a
Associative law - multiplication
a⋅(b⋅c)=(a⋅b)⋅c
Multiplicative identity
a⋅1=1⋅a=a
Multiplicative inverse
a⋅a−1=a−1⋅a=1
Communtative law - multiplication
a⋅b=b⋅a
Distributive law
a⋅(b+c)=a⋅b+a⋅c
Ok, now the rules are set and we can prove that (−a)⋅(−b)=ab.
Note that (−a)⋅(b)=−(a⋅b), so (−a)⋅(−b)+[−(a⋅b)]=(−a)⋅(−b)+(−a)⋅b =(−a)⋅[(−b)+b] =(−a)⋅0=0.
Now adding (a⋅b) to both sides gives us (−a)⋅(−b)=a⋅b.
Log in to reply
Thanks for your help XD